Using perceptions to examine human responses to blanket bans: The case of the thresher shark landing-ban in Sri Lanka. (November 2020) - Collins, Claire; Bech Letessier, Tom; Broderick, Annette; Wijesundara, Isuru; Nuno, Ana
Abstract: Species-specific bans are increasingly being implemented to stem loss of vulnerable marine species, but there is a paucity of evaluative research into resulting socio-economic and ecological consequences. In 2012, a blanket ban on landing Alopiidae (thresher) sharks was introduced in Sri Lanka. We used fisher perceptions, shown to influence support and compliance with conservation policies, to examine human responses. Data, gathered over a ten-month period in 2019 from focus groups and informal engagement during site visits, suggest support for the ban was lowest amongst fishers who perceived negative social consequences to be higher. Perceptions were also undermined by feelings of poor engagement from institutions and a lack of ecological necessity. The ban appears effective in halting targeted fisheries; however, persistent bycatch was reported by fishers. Further, bycatch appears to be widely unrecorded partly owing to mistrust and confusion amongst fishers. Occasional illegal landings were reported, seemingly motivated by interlinked factors such as good economic returns for thresher meat and high vessel running costs. The potential severity and inequity in social consequences stemming from blanket bans was highlighted, particularly when bycatch and targeted fisheries co-exist. Case study lessons are translated into a checklist containing key questions, designed to aid policy-makers to assess data provision and needs prior to introducing bans. Increasing data provision could enhance the capability of policies to predict and adapt to human behavioural responses, a key requirement considering continuing global declines in sharks despite increasing conservation effort. Highlights: Fisher perceptions highlight issues in support and compliance with thresher ban. Severe, unequal social consequences occur if targeted/bycatch fisheries co-exist. Loss of bycatch/secondary species increases fisher vulnerability to shocks. Poor uptake of discard recording protocols obscures understanding of policy impact. Polices need to be capable of predicting and adapting for human responses.